The UK's EU vote: The 1975 precedent and today's negotiations - Emmanuel Mourlon-Druol (Bruegel, 2015)
The United Kingdom's European Union Referendum Bill, introduced in the House of Commons on 28 May 2015, legislates for the holding of a referendum before 31 December 2017 on the UK's continued EU membership. UK prime minister David Cameron is opening negotiations with other EU member states to try to obtain an EU reform deal that better suits UK interests. Both the negotiations and the outcome of the referendum pose major challenges for the UK and the EU. It will not be the first time that a UK government has staged a referendum following a renegotiation of its terms of EU membership. The first such referendum took place on 5 June 1975 after nearly a year of renegotiations, and the "yes" won with 67.2 percent of the vote. Notwithstanding obvious differences, the conduct of today's renegotiations should bear in mind this precedent, and in particular consider (a) how much the UK government can get out of the negotiations, in particular with respect to potential Treaty changes; (b) why political marketing is central to the referendum's outcome; (c) how the UK administration's internal divisions risk derailing the negotiations; and (d) why the negotiations risk antagonising even the UK's best allies.
Keywords: 330